The Role of Character Education in Building Students' Ethics and Morals Through Learning The Quran and Hadith - Siti Nurjannah; Nur Hidayat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to understand the role of character education in shaping students' ethics and morals through the perspective of hadith in elementary schools, especially in the context of the times. This research uses a descriptive qualitative approach and was conducted in grade IV at a Madrasah Ibtidaiyah (MI) in Sleman during the even semester of the 2023/2024 academic year. Data were collected through observation and interviews with a teacher of Qur'an and Hadith subjects, as well as utilizing primary and secondary data. The results showed that MI in Sleman consistently develops a strong character culture, in accordance with the school's vision and mission that emphasizes strong creed, independence, noble character, and environmental insight. Character education is applied thoroughly in various school activities, although it is not specifically integrated in every subject. Teachers use storytelling methods to convey moral values to students. However, the study also identified some challenges, especially related to student behavior that does not always conform to the values taught. Overcoming these challenges requires open communication between teachers, students, and parents, as well as the establishment of clear boundaries and consistent application of consequences. The role of teachers as role models and parental involvement in children's education is very important in shaping student character. With an integrated approach and good cooperation between all parties, character education in MI in Sleman can be effective in building students' ethics and morals despite the challenges faced.